BIMAF - Bio Diversity Center - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2018)
BIMAF - Biorisk Management Facility: An innovative multi-stakeholder platform that studies the links between climate change and biotic stresses.